2010
DOI: 10.1152/japplphysiol.00996.2009
|View full text |Cite
|
Sign up to set email alerts
|

Strength training versus aerobic interval training to modify risk factors of metabolic syndrome

Abstract: Stensvold D, Tjønna AE, Skaug EA, Aspenes S, Stølen T, Wisløff U, Slørdahl SA. Strength training versus aerobic interval training to modify risk factors of metabolic syndrome. J Appl Physiol 108: 804-810, 2010. First published January 21, 2010 doi:10.1152/japplphysiol.00996.2009.-Metabolic syndrome is characterized by central obesity, elevated blood pressure, high fasting glucose and triglyceride levels, and low HDL levels. Regular physical activity can improve the metabolic profile and reduce the risks of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
252
2
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(288 citation statements)
references
References 44 publications
18
252
2
16
Order By: Relevance
“…The aerobic training-induced reduction of body fat found in the present study accompanies other evidence that aerobic exercise decreases not only body mass but also the percentage of body fat [22][23][24] . While in our data the magnitude of the reduction in body composition was between -27.7 mm to -38.5 mm of sum skinfold or -3.0% and -5.8% of fat percentage for women in OS or MN, respectively, previous studies have shown values between 0.91% and 2.93% of body fat in populations not stratified into ovulatory state and / or where other measurement techniques were used (DXA or bioimpedance) 25 .…”
Section: Discussionsupporting
confidence: 88%
“…The aerobic training-induced reduction of body fat found in the present study accompanies other evidence that aerobic exercise decreases not only body mass but also the percentage of body fat [22][23][24] . While in our data the magnitude of the reduction in body composition was between -27.7 mm to -38.5 mm of sum skinfold or -3.0% and -5.8% of fat percentage for women in OS or MN, respectively, previous studies have shown values between 0.91% and 2.93% of body fat in populations not stratified into ovulatory state and / or where other measurement techniques were used (DXA or bioimpedance) 25 .…”
Section: Discussionsupporting
confidence: 88%
“…Among the selected studies, four performed interventions in samples with eutrophic nutritional status [20][21][22][23] and five in overweight populations [24][25][26][27][28] [20][21][22][23][24][25][26] and seven cardiorespiratory fitness, specifically VO 2max in kg / ml / min. 20,22,[24][25][26][27][28] . In studies that used interval training, five used the combination of the HIIT protocol with strength training 21,[23][24][25]28 , while four adopted the SIT principles for combined training 20,22,26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…20,22,[24][25][26][27][28] . In studies that used interval training, five used the combination of the HIIT protocol with strength training 21,[23][24][25]28 , while four adopted the SIT principles for combined training 20,22,26,27 . Regarding the methodological quality of studies, one was classified as with low methodological quality 20 , six with medium quality 21,23,24,[26][27][28] and two with high quality 22,25 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations